Estudo de populações estelares de aglomerados abertos a partir de dados da missão Gaia DR2 - Filipe Andrade Ferreira (2023)
Star clusters are important objects for understanding how stars evolve. Their Color- Magnitude Diagrams (CMDs) show the effects of stellar evolution of coeval objects of same chemical composition. Furthermore, the determination of their astrophysical parameters (age, distance, color excess and metallicity) together with the spatial distribution of a sample of these objects provides information about the structure and the evolution of the Galaxy itself. In this work, we use data from Gaia DR2, 2MASS, APASS DR9 and PAN-STARRs DR1 catalogs to produce a set of methodologies for characterization of open clusters, where precise memberlists, positions, mean astrometric parameters, integrated magnitudes and radii were obtained. Using a sample of 59 open clusters with ages between 7.5 < log[t] < 9.9, we have built CMDs in the G versus GBP − GRP plane and use a cross-correlation method to compare and group CMDs of similar age to produce composite CMDs, from which we generate a set of empirical isochrones of solar metallicity, presenting an observational overview of the stellar evolution from visible to infrared within the studied age interval. Using Gaia photometry, we carried out unprecedented age calibrations based on morphological indices of CMDs based on color (∆(GBP − GRP)0 ) and magnitude (∆G) differences between the red clump and the turnoff. Our results show that PARSEC stellar evolution models present good agreement with empirical isochrones, mainly on the main sequence, where they tend to faithfully predict the difference ∆G. However, they fail to demonstrate the difference ∆(GBP − GRP)0 for ages lower than log[t] = 8.8, overestimating it. At the same time, they are systematically bluer in the low main sequence (M G > 9), especially for metallicities higher than the solar metallicity, showing that the models still present flaws in the color transformations in these luminosity intervals. Based on Gaia DR2 data, an unprecedented methodology was established for the search for new clusters in dense stellar fields based on overdensities in astrometric space. The methodology proved to be more effective than several machine learning methods, especially for sparse objects. We report the discovery of 62 new clusters with ages between 6.9 < log(t) < 9.55, distances between 910 < d(pc) < 6300 and color excess between 0.15 < E(B − V ) < 2.32, having between 10 and 600 members. The new objects are located in the Galactic disk (−200 < z < 200pc), projected mainly towards the Galactic Bulge (−10 < l < 10 deg, −5 < b < 5 deg) and are less concentrated than the average Galactic clusters.